2020
DOI: 10.17509/jpp.v20i2.24264
|View full text |Cite
|
Sign up to set email alerts
|

Tantangan dalam Penulisan Artikel Abstrak Penelitihan untuk Publikasi

Abstract: Abstrak merupakan bagian pertama yang ditinjau oleh pembaca sebelum memutuskan untuk membaca sebuah penelitihan secara keseluruhan. Dalam praktiknya, penulisan abstrak dianggap mudah sehingga kadang kurang diperhatikan. Faktanya, menulis abstrak itu sangat susah karena banyak abstrak yang kurang berkualitas. Oleh karena itu, penelitihan ini secara khusus menganalisa secara mendalam mengenai permasalahan atau tantangan yang dihadapi oleh mahasiswa S2 dalam menulis abstrak. Peneliti menggunakan desain penelitiha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…The findings of this study on students' mastery of writing journal articles align with previous research that suggests Indonesian university students struggle with writing scientific articles (Khikmah & Kurniawan, 2020;Yanti et al, 2018). Specifically, the present study found that while the students' articles received high scores, they still faced disputes in writing various sections of their articles.…”
Section: Solutions For the Students' Disputessupporting
confidence: 86%
See 3 more Smart Citations
“…The findings of this study on students' mastery of writing journal articles align with previous research that suggests Indonesian university students struggle with writing scientific articles (Khikmah & Kurniawan, 2020;Yanti et al, 2018). Specifically, the present study found that while the students' articles received high scores, they still faced disputes in writing various sections of their articles.…”
Section: Solutions For the Students' Disputessupporting
confidence: 86%
“…Specifically, the present study found that while the students' articles received high scores, they still faced disputes in writing various sections of their articles. This echoes previous research that reported difficulties in writing informative, effective, concise, and clear abstracts, finding suitable publishers, and evaluating writing (Khikmah & Kurniawan, 2020). Furthermore, students faced problems related to content, organization, and mechanics, which could be attributed to poor writing skills and flaws in study design and lack of interest (Hussain et al, 2020).…”
Section: Solutions For the Students' Disputessupporting
confidence: 79%
See 2 more Smart Citations
“…Penelitian tentang abstrak dalam sebuah artikel sudah dilakukan oleh beberapa peneliti antara lain: Anggara, Wahyono, & Nugraheni (2021); Aswir & Hasanul Misbah (2018); Bochari, Anggreni, & Basri 2022;Darmasrura, Suharni, & Afriyanti (2021); Khikmah & Kurniawan (2020). Penelitian ini memiliki letak kebaruan dibandingkan dengan penelitian sebelumnya.…”
unclassified